2007
DOI: 10.1128/jb.00900-07
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm Formation-Gene Expression Relay System inEscherichia coli: Modulation of σS-Dependent Gene Expression by the CsgD Regulatory Protein via σSProtein Stabilization

Abstract: Bacteria can switch from a single-cell (planktonic) mode to a multicellular community (biofilm) mode via production of cell-cell aggregation and surface adhesion factors. In this report, we present evidence that the CsgD protein, a transcription regulator involved in biofilm formation in Escherichia coli, modulates the expression of the rpoS ( S ) regulon. Protein pattern analysis of E. coli cells in stationary phase shows that CsgD affects the expression of several proteins encoded by S -dependent genes. CsgD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(78 citation statements)
references
References 73 publications
2
75
0
Order By: Relevance
“…A feedforward loop has been proposed for csgD in E. coli, but it has not been proven in S. Typhimurium (30). CsgD is proposed to activate the expression and synthesis of IraP, which inhibits the degradation of RpoS, thus leading to greater csgD transcription (56). RNA-seq analysis revealed that multicellular aggregates had elevated transcription of rpoS at TP2 and csgD and iraP (yaiB) at TP3 and TP4, potentially confirming this regulatory loop (see Fig.…”
Section: Resultsmentioning
confidence: 97%
“…A feedforward loop has been proposed for csgD in E. coli, but it has not been proven in S. Typhimurium (30). CsgD is proposed to activate the expression and synthesis of IraP, which inhibits the degradation of RpoS, thus leading to greater csgD transcription (56). RNA-seq analysis revealed that multicellular aggregates had elevated transcription of rpoS at TP2 and csgD and iraP (yaiB) at TP3 and TP4, potentially confirming this regulatory loop (see Fig.…”
Section: Resultsmentioning
confidence: 97%
“…The Crl protein interacts with RpoS to promote binding of the s s holoenzyme to the promoters of certain RpoS-regulated genes, including csgD (Bougdour et al, 2004;Robbe-Saule et al, 2006). IraP is transcriptionally regulated by CsgD and indirectly induces csgD through its function as an RpoS stabilizer (Gualdi et al, 2007). Finally, FliZ has been shown to reduce csgD expression by acting as an RpoS inhibitor without affecting RpoS levels (Pesavento et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Primers for real-time PCR are listed in Supplementary Table S1. RNA extraction and further reverse transcription and cDNA amplification steps were performed as described by Gualdi et al (2007), using 16S RNA as a reference gene. mRNA stability was measured by real-time PCR experiments in the presence of rifampicin, as described by Wang et al (2005).…”
Section: Methodsmentioning
confidence: 99%